The terminal lakes of the Murray River, Australia, were predominantly fresh before large-scale upstream water abstraction: Evidence from sedimentary diatoms and hydrodynamical modelling - Tibby, J.; Haynes, D.; Gibbs, M.; Mosley, L.; Bourman, R.P.; Fluin, J. (The Science of the total environment, 2022)
The Murray River is Australia's longest river, draining the continent's largest exoreic catchment. The river is Australia's most economically valuable, but is highly degraded by water extraction. The Murray River's terminal lakes, Lakes Alexandrina and Albert, formed following the mid-Holocene marine transgression. These lakes are part of one of the most ecologically important wetland ecosystems on the Australian continent and are recognised as internationally significant by the Ramsar Convention. As a result of upstream water extraction, the Lower Lakes are threatened by rising salinity. To combat this threat, water is allocated to maintain the Lower Lakes as freshwater ecosystems. This practice is part of the Murray-Darling Basin Plan, one of the largest environmental water allocation plans in the world. The water allocations and the natural history of the Lower Lakes are the subject of academic and public debate, since the water would otherwise be used for consumptive purposes, particularly irrigated agriculture, upstream. Recent modelling postulated that the lakes were saline for much of the period between 8500 and 5000 years ago. However, using new sedimentary diatom and hydrodynamic modelling evidence, we demonstrate that the Lower Lakes were fresh for most of this time, particularly after 7200 years ago. Elevated Murray River discharge between 7200 and 6600 years ago prevented sea water ingress, despite sea levels +1 m higher than present. After 6600 years ago, the lakes remained predominately fresh. Current management is, therefore, consistent with the lakes' history before European colonisation. [Display omitted] •The terminal lakes of Australia’s longest river were fresh for the bulk of their history, even when sea level was higher•Higher River Murray discharge occurred from 7200 to 6,000 years ago•Current management of the lakes to maintain their freshwater status is consistent with their geological history